2014
DOI: 10.1155/2014/752846
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Changes and Their Effects on the Value of Ecosystem Services in the Small Sanjiang Plain in China

Abstract: The small Sanjiang plain is one of the most important commodity grain production bases and the largest fresh water wetland in China. Due to the rapid expansion of agricultural activities in the past 30 years, the contradiction between economic development and the loss of ecosystem services has become an issue of increasing concern in the area. In this study, we analysed land use changes and the loss of ecosystem services value caused by these changes. We found that cropland sprawl was predominant and occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…Previous studies have indicated that LULCC has a close relationship with human activities [14,18,24,59,60] [61]. Then approximately 4.5 × 10 4 educated young people moved into the study area to work in agriculture from 1970 to 1972 in response to the call for educated youth to live in the countryside to accept poor farmers' re-education [62].…”
Section: Population Growth and Technological Progressmentioning
confidence: 99%
“…Previous studies have indicated that LULCC has a close relationship with human activities [14,18,24,59,60] [61]. Then approximately 4.5 × 10 4 educated young people moved into the study area to work in agriculture from 1970 to 1972 in response to the call for educated youth to live in the countryside to accept poor farmers' re-education [62].…”
Section: Population Growth and Technological Progressmentioning
confidence: 99%
“…By tailoring the localized average natural grain yield, the equivalent weight factor, as shown in Table 2, can be applied to different regions of China. As a benchmark, the economic value of average natural grain production of farmland per year was set at 1.0 [10,25,31,39,41,46]. Based on this factor, all other coefficients were adjusted accordingly.…”
Section: Assigning Ecosystem Service Value (Esv)mentioning
confidence: 99%
“…Several studies have been performed to monitor the impact of LULC changes on the structure and functions of ESV in numerous regions of China [4,10,18,[23][24][25][26][27][28][29][30][31][32][33] and around the world [15,25,28,29,[34][35][36][37][38][39][40][41][42][43][44][45]. Due to LULC changes and urbanization, most of these studies showed moderate to significant decrease in ESV [15,16,28,29,41,43] while others found almost no change [46].…”
mentioning
confidence: 99%
“…The total surface area is about 1.6 million ha, with 65% occupied by marshy wetland. SSP has a flat landscape with an altitude varying from 27 m to 473 m. Yearly mean temperature is relatively stable and ranges between 1.4 • C and 4.3 • C in the SSP, with the warmest month in July and the coldest month in January [49]. Annual mean precipitation ranges between 500 mm and 650 mm in this region.…”
Section: Study Areamentioning
confidence: 99%